Hepatitis B Virus X Protein Function Requires Zinc Binding - Ramakrishnan, Dhivya; Xing, Weimei; Beran, Rudolf K; Chemuru, Saketh; Rohrs, Henry; Niedziela-Majka, Anita; Marchand, Bruno; Mehra, Upasana; Zábranský, Aleš; Doležal, Michal; Hubálek, Martin; Pichová, Iva; et al. (Journal of virology, 2019)
The host structural maintenance of chromosomes 5/6 complex (Smc5/6) suppresses hepatitis B virus (HBV) transcription. HBV counters this restriction by expressing the X protein (HBx), which redirects the cellular DNA damage-binding protein 1 (DDB1)-containing E3 ubiquitin ligase to target Smc5/6 for degradation. However, the details of how HBx modulates the interaction between DDB1 and Smc5/6 remain to be determined. In this study, we performed biophysical analyses of recombinant HBx and functional analysis of HBx mutants in HBV-infected primary human hepatocytes (PHH) to identify key regions and residues that are required for HBx function. We determined that recombinant HBx is soluble and exhibits stoichiometric zinc binding when expressed in the presence of DDB1. Mass spectrometry-based hydrogen-deuterium exchange and cysteine-specific chemical footprinting of the HBx:DDB1 complex identified several HBx cysteine residues (located between amino acids 61 and 137) that are likely involved in zinc binding. These cysteine residues did not form disulfide bonds in HBx expressed in human cells. In line with the biophysical data, functional analysis demonstrated that HBx amino acids 45 to 140 are required for Smc6 degradation and HBV transcription in PHH. Furthermore, site-directed mutagenesis determined that C61, C69, C137, and H139 are necessary for HBx function, although they are likely not essential for DDB1 binding. This CCCH motif is highly conserved in HBV as well as in the X proteins from various mammalian hepadnaviruses. Collectively, our data indicate that the essential HBx cysteine and histidine residues form a zinc-binding motif that is required for HBx function.IMPORTANCE The structural maintenance of chromosomes 5/6 complex (Smc5/6) is a host restriction factor that suppresses HBV transcription. HBV counters this restriction by expressing HBV X protein (HBx), which redirects a host ubiquitin ligase to target Smc5/6 for degradation. Despite this recent advance in understanding HBx function, the key regions and residues of HBx required for Smc5/6 degradation have not been determined. In the present study, we performed biochemical, biophysical, and cell-based analyses of HBx. By doing so, we mapped the minimal functional region of HBx and identified a highly conserved CCCH motif in HBx that is likely responsible for coordinating zinc and is essential for HBx function. We also developed a method to produce soluble recombinant HBx protein that likely adopts a physiologically relevant conformation. Collectively, this study provides new insights into the HBx structure-function relationship and suggests a new approach for structural studies of this enigmatic viral regulatory protein.
Keywords: DNA vazebné proteiny; trans-aktivátory; Hepatitis B; vazebná místa; Amino Acid Motifs; virus hepatitidy B; sekvence aminokyselin; Recombinant Fusion Proteins; Trans-Activators; vazba proteinů; hepatitida B; rekombinantní fúzní proteiny; lidé; Zinc; Amino Acid Sequence; zinek; DNA-Binding Proteins; interakce hostitele a patogenu; Amino Acids; Host-Pathogen Interactions; aminokyseliny; Hepatitis B virus; aminokyselinové motivy; Protein Binding; Binding Sites; Humans